Implementasi Peraturan Daerah Kota Medan No. 3 Tahun 2011 tentang Pajak Bumi Dan Bangunan Di Badan Pengelola Pajak Dan Retribusi Daerah Kota Medan - Suci Rahmadani Hasibuan; Adam Adam; Nina Angelia (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2022)
This study aims to find out how BPPRD currently implements Medan City Regulation Number 3 of 2011 concerning Land and Building Tax. The researcher uses George C. Edward III's implementation theory in his research (communication, resources, disposition and bureaucratic structure). This type of research consists of qualitative research using observation, interviews and recording methods to obtain materials. This study reminds land and tax staff as well as taxpayers. The findings show that the Medan City Regional Regulation Number 3 of 2011 concerning the Land and Building Tax Subdivision of the Medan City BPPRD is strictly enforced and implemented by the competent authorities. Despite public awareness of the need to pay taxes, there are substantial barriers to implementation, including poor collection and communication by tax authorities..